2017
DOI: 10.1002/dev.21551
|View full text |Cite
|
Sign up to set email alerts
|

The intersensory redundancy hypothesis: Extending the principle of unimodal facilitation to prenatal development

Abstract: Selective attention to different properties of stimulation provides the foundation for perception, learning, and memory. The Intersensory Redundancy Hypothesis (IRH) proposes that early in development information presented redundantly across two or more modalities (multimodal) selectively recruits attention to and enhances perceptual learning of amodal properties, whereas information presented to a single sense modality (unimodal) enhances perceptual learning of modality-specific properties. The present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…In contrast, chicks receiving redundant bimodal (audiovisual) exposure did not prefer that familiarized call over the same call with altered pitch. In other words, when the pitch range was narrowed and the detection of the pitch change became more difficult, unimodal facilitation was observed, as was the case in our original prenatal study (Lickliter et al, 2017) with younger, less experienced quail.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…In contrast, chicks receiving redundant bimodal (audiovisual) exposure did not prefer that familiarized call over the same call with altered pitch. In other words, when the pitch range was narrowed and the detection of the pitch change became more difficult, unimodal facilitation was observed, as was the case in our original prenatal study (Lickliter et al, 2017) with younger, less experienced quail.…”
Section: Resultsmentioning
confidence: 54%
“…As was the case in our original prenatal study (Lickliter et al., 2017), the data of interest for analyses were measures of duration (in seconds) of proximity to the two auditory stimuli presented during testing. A proportion of total duration time (PTDT) was calculated from the time a chick spent in the approach area containing the familiar version of the maternal call relative to the total duration spent in both familiar and modified approach areas.…”
Section: General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quail embryos receiving exposure to a range of species-atypical auditory stimuli in the week prior to hatching showed reduced species-specific perceptual (auditory) narrowing when compared to control chicks in the week following hatching. In addition, we found that quail embryos exposed to acoustically modified maternal vocalizations prenatally could generalize this familiarization experience and show modified postnatal auditory preferences for maternal vocalizations (Lickliter, Bahrick, & Vaillant-Mekras, 2017). Taken together, these findings underscore the sensitivity of the bird embryo to variations in prenatal experience and point to the range of postnatal consequences of modified prenatal experience.…”
Section: Exploring the Role Of Prenatal Sensory Experience On Perceptmentioning
confidence: 99%